Effects of Low- and High-Dose Chemotherapy Agents on Thrombogenic Properties of Extracellular Vesicles Derived from Breast Cancer Cell Lines - Aharon, Anat; Sabbah, Anni Rebibo; Issman, Liron; Berkovich, Hila; Copty, Reem; Talmon, Yeshayahu; Brenner, Benjamin (Thrombosis and Haemostasis, 2018)
Background The involvement of extracellular vesicles (EVs) in cancer-associated thrombosis (CT) is unclear. This study aimed to explore the properties of EVs derived from breast cancer (BC) cells following exposure to high- or low-dose chemotherapeutic agents and evaluate thrombogenic effects of these EVs on endothelial cells (ECs).Methods EVs were isolated from BC cell lines (non-metastatic MCF7, high-metastatic MDA-MB-231), pre-exposed to serum-free medium (control), with or without increasing doses of doxorubicin or paclitaxel. EV structure and size were studied using electron microscopy and Nano-sight. Antigen levels were measured by fluorescence-activated cell sorting (FACS). EV effects on EC thrombogenicity were assessed using FACS, factor Xa chromogenic assay and RT-PCR.Results Serum-free medium BC cell resulted in EV shedding that additionally increased when MDA-MB-231 cells were exposed to high doses of both agents. Tissue factor (TF) levels were similarly low (9–13%) in all EVs compared with the high expression on their parental MDA-MB-231 cells (76–83%). EVs derived from MDA-MB-231 cells stimulated with high-dose doxorubicin demonstrated significantly (fivefold; p < 0.001) elevated levels of negatively charged phospholipids, a 97% decrease in TF pathway inhibitor (TFPI) levels and a sixfold increase (p < 0.001) in procoagulant activity. These EVs also enhanced EC thrombogenicity. Effects of EVs originating from MCF7 cells were less pronounced.Conclusion These findings suggest that thrombogenic properties of BC-derived EVs may depend on the type and dose of the applied chemotherapy agent and may also be affected by the cell metastatic nature.
Keywords: extracellular vesicles; breast cancer cells; endothelial cells; high-dose chemotherapy; thrombogenicity